Collision-free trajectory planning for dual-robot systems using B-splines. (23rd August 2017) - Chen, Youdong; Li, Ling
This article presents a new approach for planning collision-free trajectories of two robots working in a shared workspace. Based on the B-spline knot refinement and the local modification scheme, the approach only changes the local trajectory around the collision area without changing the shape in the global way. The geometric model of dual-robot is employed by two kinds of geometric elements (sphere and capsule). A collision check method calculates the distance between two robots to determine whether the collisions exist. The collision check is converted to calculate the distance between every two elements. The proposed method has been implemented on a dual-robot system composed of two KUKA manipulators. The numerical and simulation results presented in the article illustrate the efficiency of the proposed technique.